Marketing Thailand's potatoes: Present patterns and future prospects. - Scott, G. J. (1987)
This study analyzes the marketing patterns for Thailand's potatoes in order to assess future commercial prospects for this crop both at home and abroad. The report utilizes a food systems approach as an analytical framework. Thus, potato marketing activities are scrutinized in the context of potato production and consumption patterns. Informal interviews with growers, traders and consumers carried out in 1984 in Thailand and Singapore served as one source of data for this report. A literature review and official statistics provided further information. Results emphasize the unusual features of potato marketing in Thailand, e.g. the importance of hotels and restaurants in the marketing chain. Additional findings such as high retail marketing margins are likely to be thought provoking for other Southeast Asian countries as well. Recommendations suggest that to address marketing problems efforts to develop production and consumption should be undertaken simultaneously.